USE AN UNPOPULAR METHOD TO FIND THE TRUE SIZE OF A PLANE IN THE GENERAL CASE - Mustafa Aminbaevich Karimov; Bakhtiyor Botirovich Yuldashev; Tavakkalova Sevara Odilbek qizi; Asadova Mohlaroyim Otabek qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Methods of alternating planes, moving in parallel parallel, and rotating around a vertical line. As always, the topic of “Determining the True Size of a Plane in a General Situation” is analyzed using the simplest visual graphs to explain to students.